Uma estratégia simplificada para a seleção da carga em testes de endurance de alta intensidade para avaliação de resposta terapêutica em pacientes com DPOC - Costa, Luiza Helena Degani [UNIFESP] (2018)
Time to limitation (Tlim) in response to constant work rate (CWR) is sensitive to interventions in chronic obstructive pulmonary disease (COPD). Although a recent European Respiratory Society taskforce recommended a pre-intervention test lasting 3 to 8 min (Tlim3’-8’), there is no simple method to select a CWR consistently associated with Tlim3’-8’. The aims of the present study were to validate a pragmatic strategy to select a work rate (WR) associated with Tlim3’-8’, and to assess reproducibility and responsiveness of the resulting CWR3’-8’ test. We assessed 59 GOLD stages II – IV COPD patients, who initially cycled to Tlim at 75% peak (WRpeak). In case of short (< 3 min, low-endurance) or long (> 8 min, high-endurance) tests, patients exercised after 60 min at 50% or 90%, respectively. Critical mechanical constraints and limiting dyspnea at 75% were reached within the desired timeframe in 27 “mid-endurance” patients (45.7%). Decreasing or increasing CWR intensity slowed or hastened, respectively, the mechanicalventilatory responses; thus, similar physiological and sensory limits were reached at Tlim3’-8’ in 5/6 “low-endurance” and 23/26 “high-endurance” patients. Overall, Tlim3’-8’ was obtained in all but 4 patients (93.2%) with this CWR50%⇐75%⇒90% strategy. On the other hand, applying higher (60%) or lower (80%) WR intensities failed to consistently produce Tlim3’-8’ in “low-” and “high-endurance” subjects, respectively (p>0.05). Repeating CWR3’-8’ in a subgroup of patients (n=12) following nebulized placebo allowed to demonstrate that Tlim had good reproducibility, with endurance time remaining within the desired range in all subjects. Moreover, when the same patients repeated CWR3’-8’ following nebulized bronchodilators, there was a median (IQR) increase in Tlim of 190 (30 – 365) s (p < 0.05). This simplified approach to individualized work rate adjustment (CWR50%⇐75%⇒90%) successfully elicited critical mechanical constraints and limiting dyspnea within the time limits currently recommended in clinical trials in COPD (Tlim3’-8’), leading to tests that were reproducible and responsive to interventions.